Model dan Etika Pengambilan Keputusan dalam Kepemimpinan Lembaga Pendidikan Islam - Ubaidah Qoriatus Zahidah; Rofiatul Azkiyah; Firman Kurniawan; Mu’alimin (CV. ITTC INDONESIA, 2025)
This study examines decision-making models and ethics in the leadership of Islamic educational institutions through a qualitative literature review approach. The research focuses on identifying and analyzing decision-making processes that integrate Islamic values, such as deliberation (syura), justice, honesty (as-siddiq), and trustworthiness (amanah). Data were collected from SINTA-indexed journal articles published between 2019 and 2024, with keywords including